Delineation of human prostate cancer evolution identifies chromothripsis as a polyclonal event and FKBP4 as a potential driver of castration resistance. Issue 1 (2nd April 2018) - Federer‐Gsponer, Joël R; Quintavalle, Cristina; Müller, David C; Dietsche, Tanja; Perrina, Valeria; Lorber, Thomas; Juskevicius, Darius; Lenkiewicz, Elisabeth; Zellweger, Tobias; Gasser, Thomas; Barrett, Michael T; Rentsch, Cyrill A; et al.
Abstract: Understanding the evolutionary mechanisms and genomic events leading to castration‐resistant (CR) prostate cancer (PC) is key to improve the outcome of this otherwise deadly disease. Here, we delineated the tumour history of seven patients progressing to castration resistance by analysing matched prostate cancer tissues before and after castration. We performed genomic profiling of DNA content‐based flow‐sorted populations in order to define the different evolutionary patterns. In one patient, we discovered that a catastrophic genomic event, known as chromothripsis, resulted in multiple CRPC tumour populations with distinct, potentially advantageous copy number aberrations, including an amplification of FK506 binding protein 4 (FKBP4, also known as FKBP52), a protein enhancing the transcriptional activity of androgen receptor signalling. Analysis of FKBP4 protein expression in more than 500 prostate cancer samples revealed increased expression in CRPC in comparison to hormone‐naïve (HN) PC. Moreover, elevated FKBP4 expression was associated with poor survival of patients with HNPC. We propose FKBP4 amplification and overexpression as a selective advantage in the process of tumour evolution and as a potential mechanism associated with the development of CRPC. Furthermore, FKBP4 interaction with androgen receptor may provide a potential therapeutic target in PC. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.